The Influence of Inventory Round Ratio and Activities Round Ratio of Profitability (ROI) - Lina Nofiana; Denok Sunarsi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the effect of Turnover Ratio and Asset Turnover Ratio on Profitability (ROI) at PT. HM Sampoerna Tbk Period 2009-2018. The method used is explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression testing, evaluation, determination and hypothesis testing. The results of this study indicate that a significant Turnover Ratio to Profitability (ROI) of 91.8%, the hypothesis test obtained a significance of 0,000 <0.05. Asset Turnover Ratio has a significant effect on profitability (ROI) of 96.3%, hypothesis testing obtained significance of 0,000 <0.05. Planning Turnover Ratio and Activation Turnover Ratio significantly to Profitability (ROI) of 96.5%, the hypothesis test obtained significance of 0,000 <0.05.